AGGLOMERATION FOR SMALL AND MEDIUM FOOD ENTERPRISES PERFORMANCE MEASUREMENT - Eunike, Agustina (JEMIS (Journal of Engineering & Management in Industrial System), 2015)
Abstract Geographic proximity to similar enterprises has become one of SMEs strategy in order to enhance their market. The proximity is usually called agglomeration or cluster industry. Hence, the aim of this paper is to measure performance of SMEs agglomeration. Performance measurement framework is designed using BSC with four perspective of measurement, thus are social, environment, financial, and internalbusiness processes. The assessment is executed using AHP which is presented based on the designed BSC framework. The measure is applied to an area in Malang city named Sanan which consist of SMEs produce and sell product relate to Keripik Tempe. The study reveals that agglomeration is success to increase all the cluster performance. The cluster performance is good with 75,70% achievement of their key performance indicator. Based on each perspective, the best performance achieve by social aspect that is 78,07% of the target, and the lowest one is economic aspect with 70,42% achievement.